AKUNTABILITAS DAN TRANSPARANSI TERHADAP PUBLIC TRUST DALAM PENGELOLAAN KEUANGAN DI KLASIS PORT NUMBAY - Patty, Brigitte Liony; Mulyadi, JMV; Sailendra; Harnovinsah; Ahmar, Nurmala (APSSAI, 2024)
This research aims to test and analyze whether accountability and transparency influence public trust in the financial management of the Klasis Port Numbay with religiosity as a moderating variable. This research uses quantitative research methods using the WarpPLS 7.0 application. The population is GKI churches located within the Klasis Port Numbay office environment, with the sample being the chairman of the congregation council, the congregation treasurer, and several congregation members with the qualifications to understand church financial management. The data analysis tests in this research are descriptive statistical tests, measurement models (outer models), inner model analyses, and hypothesis testing. The research results show that accountability and transparency positively and significantly affect public trust in financial management. Religiosity can moderate accountability toward public trust in financial management, and religiosity can moderate transparency toward public trust in financial management.